2015
DOI: 10.5935/0004-2749.20150019
|View full text |Cite
|
Sign up to set email alerts
|

Ketorolac eye drops reduce inflammation and delay re-epithelization in response to corneal alkali burn in rabbits, without affecting iNOS or MMP-9

Abstract: Purposes: To assess the effects of 0.5% ketorolac tromethamine without preservatives on the expression of iNOS and MMP-9 in alkali burn ulcers. Methods: Twelve eyes of 120-day-old male rabbits were treated (TG) every 6 h with 0.5% ketorolac tromethamine and 12 other eyes were treated with saline solution (CG), immediately after the occurrence of ulcers by 1 M sodium hydroxide (NaOH). Re-epithelialization was monitored using fluorescein every 6 h. After 24 h, six corneas (n=6) of each group were collected (M1).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…However, another study reported that diclofenac, meloxicam, and celecoxib have variable antioxidant effects, decreasing blood levels of MDA and increasing blood levels of SOD in human patients with rheumatoid arthritis 31 . In the ophthalmology field, one study showed that the same FKT solution used herein reduced the inflammation and delayed the epithelialization of the cornea of rabbits without impacting the expression of the inducible isoform of nitric oxide or MMP‐9 47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study reported that diclofenac, meloxicam, and celecoxib have variable antioxidant effects, decreasing blood levels of MDA and increasing blood levels of SOD in human patients with rheumatoid arthritis 31 . In the ophthalmology field, one study showed that the same FKT solution used herein reduced the inflammation and delayed the epithelialization of the cornea of rabbits without impacting the expression of the inducible isoform of nitric oxide or MMP‐9 47 …”
Section: Discussionmentioning
confidence: 99%
“…31 In the ophthalmology field, one study showed that the same FKT solution herein reduced the inflammation and delayed the epithelialization of the cornea of rabbits without impacting the expression of the inducible isoform of nitric oxide or MMP-9. 47 To our knowledge, this is the first study that reports the results of biomarkers of oxidative stress in the conjunctiva of dogs treated with TK. One study reported that during aging, SOD1-knockout mice develop a cumulative oxidative stress status that induces squamous metaplasia of the conjunctival epithelium, with a consequent reduction in TFBT.…”
Section: Baselinementioning
confidence: 94%
“…Weitere tierexperimentelle Studienvorwiegend an alkaliverätzten Hornhäutenbelegen u. a. hohe Aktivitäten lysosomaler Enzyme nach der Leukozyteninfiltration in die Hornhaut [33], führten zur Identifizierung weiterer Entzündungsmediatoren [34] und erbrachten den Nachweis des Zusammenhangs zwischen reduzierter Entzündungsreaktion, gedrosseltem Leukozyteneinstrom, beschleunigter Reepithelisierung und verringerter Fibrosierung des Gewebes [35]. In einer Vielzahl von Studien erwies sich im Tierexperiment, aber auch an humanen limbalen epithelialen Stammzellkulturen, die Wirksamkeit diverser lokal, aber auch systemisch applizierter steroidaler und nicht steroidaler Antiphlogistika sowie antiangionetischer Substanzen zur Therapie der Augenverätzung [11,20,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Dieser Therapieansatz einer antientzündlichen und damit auch antiangiogenetischen Behandlung hat damit in der klinischen Praxis einen zentralen Stellenwert.…”
Section: Pathophysiologische Mechanismen Und Therapieansätzeunclassified
“…MMP-12 may disintegrate certain components of the extracellular matrix (ECM) released following severe alkali burn, which may be involved in ECM remodeling ( 129 ). Inhibiting alkali burn-induced CNV by accelerating corneal wound healing and by reducing the production of angiogenic factors, inflammatory cytokines and MMPs may be a potential therapeutic strategy ( 29 , 125 , 130 133 ). PPAR-γ agonists are able to affect proliferation, differentiation, apoptosis and inflammation in different cell types.…”
Section: Potential Role Of Ppar Agonists In the Treatment Of Cabmentioning
confidence: 99%